Iridescence Reveals the Formation and Growth of Ice Aerosols in Martian Noctilucent Clouds - M. T. Lemmon; A. Vicente‐Retortillo; S. D. Guzewich; M. de la Torre Juárez; A. C. Innanen; C. L. Campbell; J. N. Maki; M. C. Malin; J. E. Moores (Geophysical Research Letters)
Abstract Water and carbon dioxide each form mesospheric clouds on Mars. At such altitudes (40–100 km), clouds may remain sunlit for part of the night. We describe a previously unreported, visually spectacular season of iridescent, noctilucent clouds visible in early southern autumn from the Curiosity rover's site in Gale crater. Ice nucleation begins near sunset with a narrow range of particle sizes, and the ice aerosols grow and precipitate. The iridescence, visible through three‐color imaging, arises from locally uniform particle sizes resulting from similar growth histories. Colorful fall streaks show the clouds evolving, and a scattering corona shows size uniformity over large areas. The terminator was observed on the clouds, allowing the determination of cloud altitudes and a likely CO2 composition. This is the first observation of particle size variations within individual Martian clouds, allowing a new probe of Martian cloud physics.